1999
DOI: 10.1111/j.1740-8261.1999.tb00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Age and Diet Effects on Relative Renal Echogenicity in Geriatric Bitches

Abstract: Under controlled, but varied dietary conditions 35 geriatric, uninephrectomized, spayed Beagle bitches (dogs) observed for 4 years, renal cortical and renal medullary echogenicity was measured relative to hepatic and splenic echogenicity. Regardless of the diet fed, 60-75% of these aged dogs had renal cortical echogenicity less than that of either the liver or spleen across time; 25-35% of these dogs had renal cortical echogenicity equal to that of the liver, but less than that of the spleen across time. Less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…These results were in agreement with (Braun 1991;1993). Wood (1990) and Churchill (1999) in their studies in dogs found that the renal medulla was always hypoechoic compared to the cortex, uniformly mottled echogenicity of the renal cortex could be clearly differentiated from the less echogenic renal medulla. In this study, the renal cortex was hyperechoic in comparison to the relative hypoechoic renal medullary pyramids in left kidney, however, the cortex and medulla could not be differentiated in right kidney.…”
Section: Discussionsupporting
confidence: 90%
“…These results were in agreement with (Braun 1991;1993). Wood (1990) and Churchill (1999) in their studies in dogs found that the renal medulla was always hypoechoic compared to the cortex, uniformly mottled echogenicity of the renal cortex could be clearly differentiated from the less echogenic renal medulla. In this study, the renal cortex was hyperechoic in comparison to the relative hypoechoic renal medullary pyramids in left kidney, however, the cortex and medulla could not be differentiated in right kidney.…”
Section: Discussionsupporting
confidence: 90%
“…The spleen was used as the main organ of comparison in the current study, but it was not always possible to examine the splenic parenchyma at the same depth as the kidney, and this could have affected interpretation of renal echogenicity in some cases. In the recent years, qualitative and quantitative studies on the cortical echogenicity and the effect of artifacts on its intensity have been performed in healthy dogs. Two more recent publications have tried to eliminate patient and technical related biases, avoiding the comparison with other organs and analyzing the mean gray value in ex vivo and in vivo kidneys under standardized experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Subjective evaluation included the following variables: cortical echogenicity, medullary echogenicity, and kidney shape/contour . The subjective abnormalities detected were graded according to severity using a grading system created for the study, but based on the veterinary kidney ultrasound literature . Kidney severity grades were: grade 0 for normal appearance, grade 1 for mild abnormality, grade 2 for moderate abnormality, and grade 3 for severe abnormality.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations